Ciência da informação em perspectiva histórica: Lydia de Queiroz Sambaquy e o aporte da Documentação (Brasil, 1930-1970) - Oddone, Nanci Elizabeth (2004)
Since its first disciplinary documents Information Science stressed its distinction from Librarianship. During the last forty years however what can be seen is a straight closeness between them. This research looks through the history of Librarianship in Brazil during the period from 1930 to 1970. It stresses the role of Lydia de Queiroz Sambaquy at the Library of DASP, as the coordinator of SIC and as president of the early IBBD. The main argument says when Information Science was introduced in Brazil it followed many of Sambaquy s ideas involving Librarianship and Documentation. The historical and primary documents analyzed by this research lead to the conclusive idea that earlier than 1970 the concepts which form the base of Information Science were already functioning at IBBD under the leadership of Lydia Sambaquy